2018
DOI: 10.1293/tox.31.1s
|View full text |Cite
|
Sign up to set email alerts
|

Nonproliferative and Proliferative Lesions of the Rat and Mouse Endocrine System

Abstract: The INHAND (International Harmonization of Nomenclature and Diagnostic Criteria for Lesions in Rats and Mice) Project (www.toxpath.org/inhand.asp) is a joint initiative among the Societies of Toxicological Pathology from Europe (ESTP), Great Britain (BSTP), Japan (JSTP) and North America (STP) to develop an internationally accepted nomenclature for proliferative and nonproliferative lesions in laboratory animals. The purpose of this publication is to provide a standardized nomenclature for classifying microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 208 publications
(277 reference statements)
1
54
0
Order By: Relevance
“…When we tested how pituitary-thyroid-periphery signaling responds to orchidectomy in our middle-aged rat model, unchanged serum l-thyroxine (T 4 ) and TSH were detected [127]. On the other hand, liver Dio 1 and pituitary Dio 2 enzyme activities were decreased, which indicated a local hypothyroid state, in line with altered cytomorphology of thyrotropic cells, which appeared enlarged and vacuolated, as in hypothyroid states [122]. In addition to this, most recently, specific cell-type transcriptomic analysis showed that 100% of sex-dominant genes in TSH cells were male-dominant [16].…”
Section: Effects Of Estradiol On Tsh Cells In Males and Putative Chanmentioning
confidence: 91%
See 1 more Smart Citation
“…When we tested how pituitary-thyroid-periphery signaling responds to orchidectomy in our middle-aged rat model, unchanged serum l-thyroxine (T 4 ) and TSH were detected [127]. On the other hand, liver Dio 1 and pituitary Dio 2 enzyme activities were decreased, which indicated a local hypothyroid state, in line with altered cytomorphology of thyrotropic cells, which appeared enlarged and vacuolated, as in hypothyroid states [122]. In addition to this, most recently, specific cell-type transcriptomic analysis showed that 100% of sex-dominant genes in TSH cells were male-dominant [16].…”
Section: Effects Of Estradiol On Tsh Cells In Males and Putative Chanmentioning
confidence: 91%
“…Sex steroids affect the feedback response of TSH cells to free thyroid hormone concentrations in blood diversely in male and female rodents [121,122]. Male rats have higher TSH values and are more prone to develop thyroid diseases (or even thyroid carcinoma) in response to goitrogenic agents compared with females [121,122]. In humans, sex-related differences in TSH values are not as clearly visible as in rodents, but women are more prone to thyroid dysfunctions in comparison with men.…”
Section: Effects Of Estradiol On Tsh Cells In Males and Putative Chanmentioning
confidence: 99%
“…Within the cystic cavities, there was also a multifocal accumulation of cholesterol clefts and clusters of foamy macrophages ( The atypical and highly proliferative epithelium were characteristic of epithelial neoplasia. Given its location, the compression of the brain, and the presence of papillary projections lined by squamous epithelium with hyperkeratosis, the diagnosis was compatible with a craniopharyngioma (CP) 1 .…”
Section: Main Textmentioning
confidence: 99%
“…CPs and RCCs both originate in Rathke's pouch, and therefore arise from a common epithelial lining: cuboidal, ciliated epithelium, often containing mucus and goblet cells 1,19 . Histopathology is one of the most reliable tools for differential diagnosis; however, differentiating among RCCs and CPs can be challenging as some of the histological features overlap 8 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation